Positive electrode active material and lithium secondary battery including same
By physically mixing boron-containing compounds with lithium-rich lithium manganese-based oxides to form lithium manganese-based oxides in a specific space group, the problem of insufficient electrochemical performance and stability in lithium secondary batteries is solved, and higher electrochemical performance and stability is achieved, especially suitable for high voltage environments.
Patent Information
- Application Number
- CN202380066905.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-19
- Filing Date
- 2023-08-31
- Publication Date
- 2025-04-25
AI Technical Summary
The existing lithium-rich lithium manganese-based oxide positive electrode active substances have problems with insufficient electrochemical performance and stability in lithium secondary batteries, especially in high voltage storage or working environments, which can easily lead to reduced rate characteristics and shortened service life.
By physically mixing the boron-containing compound with lithium-rich lithium manganese oxides, a positive electrode active material containing solid solution or complex of the C2/m space group and the R3-m space group is formed, which inhibits or alleviates the dissolution of the transition metal and reduces the side reaction with the electrolyte.
It effectively improves the electrochemical performance and stability of lithium secondary batteries, prevents abnormal resistance and deterioration of life due to transition metal dissolution, especially in high voltage environments, reducing gas generation.
Smart Images

Figure CN119895592A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material and a lithium secondary battery including the positive electrode active material. More specifically, the present invention relates to a positive electrode active material and a lithium secondary battery including the positive electrode active material. The positive electrode active material is a positive electrode active material including a lithium-rich lithium manganese-based oxide, which can prevent the reduction of the electrochemical characteristics of the lithium secondary battery including the rate characteristics due to the excessive presence of lithium and manganese in the lithium manganese-based oxide. In particular, the life of the lithium secondary battery can be prevented from being reduced by inhibiting or reducing the dissolution of transition metals from the lithium manganese-based oxide. Background Art
[0002] Batteries use materials that can undergo electrochemical reactions at the positive and negative electrodes to store electrical energy. A typical example of such batteries is a lithium secondary battery that stores electrical energy through the chemical potential difference when lithium ions are inserted / released between the positive and negative electrodes.
[0003] The lithium secondary battery is prepared by using a substance capable of reversibly inserting and extracting lithium ions as a positive electrode active material and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.
[0004] Representative materials used as positive electrode active materials for lithium secondary batteries include lithium composite oxides. Examples of the above-mentioned lithium composite oxides include LiCoO2, LiMn2O4, LiNiO2, LiMnO2, or complex composite oxides of nickel, cobalt, manganese or aluminum as disclosed in Korean Patent Publication No. 10-2015-0069334 (published on June 23, 2015).
[0005] Among the above-mentioned positive electrode active materials, LiCoO2 is the most widely used due to its excellent life characteristics and charge and discharge efficiency, but its price competitiveness is limited due to the resource limitation of cobalt used as a raw material and its high price.
[0006] Lithium manganese-based oxides such as LiMnO2 and LiMn2O4 have the advantages of excellent thermal stability and low price, but have problems of small capacity and poor high-temperature characteristics. In addition, LiNiO2-based positive electrode active materials have battery performance with high discharge capacity, but are difficult to synthesize due to the cation mixing problem between lithium and transition metals, resulting in major problems in rate characteristics.
[0007] Furthermore, depending on the severity of such cation mixing, a large amount of lithium byproducts are generated, most of which are composed of compounds of LiOH and Li2CO3, so when preparing the positive electrode slurry, it leads to gelation, or after preparing the electrode, it may become a cause of gas generation due to repeated charge and discharge. In addition, the residual Li2CO3 in the above lithium byproducts increases the swelling phenomenon of the monomer and becomes a cause of reducing the service life.
[0008] Various candidate materials are being discussed for compensating for the shortcomings of these existing positive electrode active materials.
[0009] For example, research is underway to use lithium-rich manganese-based oxides containing excess manganese in transition metals and a lithium content greater than the total content of transition metals as positive electrode active materials for lithium secondary batteries. Such lithium-rich manganese-based oxides are also called overlithi ated layered oxides (OLO).
[0010] Although the above OLO has the advantage of showing high capacity under high voltage working environment in theory, in reality, due to the excessive manganese contained in the oxide, its conductivity is relatively low, so there is a disadvantage that the rate characteristic of the lithium secondary battery using OLO is low. As mentioned above, when the rate characteristic is low, the charge / discharge capacity and life efficiency (cycle capacity retention) deteriorate during the cycle of the lithium secondary battery.
[0011] In order to solve the above problems, studies have been conducted to change the composition of OLO, but these attempts have not yet reached the level of commercialization. Summary of the invention
[0012] Technical issues
[0013] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles plays a leading role in the market, and the demand for positive electrode active materials used in lithium secondary batteries is also constantly changing.
[0014] For example, in the prior art, lithium secondary batteries using lithium iron phosphate (LFP) are mainly used from the viewpoint of ensuring safety, etc., but recently, the use of nickel-based lithium composite oxides having a larger energy capacity per unit weight than LFP has been expanded.
[0015] In addition, nickel-based lithium composite oxides, which are mainly used as positive electrode active materials for high-capacity lithium secondary batteries in recent years, must use ternary metal elements such as nickel, cobalt and manganese or nickel, cobalt and aluminum. However, since cobalt is not only unstable in supply and demand but also too expensive compared to other raw materials, a positive electrode active material with a new composition that can reduce the cobalt content or does not contain cobalt is needed.
[0016] Taking the whole situation into consideration, although lithium-rich lithium manganese-based oxides can meet the expectations of the above-mentioned market, the above-mentioned lithium manganese-based oxides still have the limitation of lacking electrochemical performance or stability in replacing commercial positive electrode active materials such as ternary lithium composite oxides composed of nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA).
[0017] For example, compared with ternary lithium composite oxides, lithium manganese-based oxides are more likely to have transition metals eluted from the particle surface during repeated charge and discharge. In particular, manganese contained in excess in lithium manganese-based oxides is more likely to be eluted from the particle surface.
[0018] When the transition metal is eluted from the lithium manganese-based oxide, the eluted transition metal may react with the electrolyte on the surface of the lithium manganese-based oxide to form impurities. The impurities not only increase the surface resistance of the lithium manganese-based oxide, but also become the cause of reducing the insertion / extraction efficiency of lithium ions through the lithium manganese-based oxide.
[0019] Furthermore, transition metals dissolved from the above-mentioned lithium manganese-based oxide or impurities formed by the reaction of the dissolved transition metals with the electrolyte may move to the negative electrode through the electrolyte as a medium and may be deposited on the surface of the negative electrode.
[0020] For example, due to a side reaction between the surface of the lithium manganese-based oxide and the electrolyte or a structural change (crystal structure change, etc.) of the lithium manganese-based oxide, the excessive amount of Mn contained in the lithium manganese-based oxide may be 2+ Mn dissolved in the electrolyte may be dissolved in the electrolyte. 2+ During the formation or charge-discharge process, the electrolyte may move to the negative electrode surface, thereby reacting with various substances (electrons, electrolyte, electrodes or by-products, etc.) present in the battery. As a result, Mn 2+ , Mn metal or Mn-containing compounds (e.g., MnCO3, MnO, MnF2, etc.) impurities exist.
[0021] Transition metals or impurities deposited on the surface of the negative electrode will rapidly increase the resistance of the negative electrode. This resistance anomaly is a representative cause of accelerated deterioration of the life of lithium secondary batteries.
[0022] In particular, in the case of a lithium secondary battery using the above-mentioned lithium manganese-based oxide as a positive electrode active material, the operating voltage is higher than that of a lithium secondary battery using other commercially available ternary lithium composite oxides as a positive electrode active material, so the above-mentioned problem is likely to occur.
[0023] However, there is currently no technology for addressing the dissolution of transition metals from lithium-rich lithium manganese-based oxides and the problems arising therefrom.
[0024] As mentioned above, compared with other types of commercially available positive electrode active materials, existing lithium-rich lithium manganese-based oxides have disadvantages in electrochemical performance and / or stability.
[0025] However, the inventors of the present invention have confirmed that when an additive capable of inhibiting or alleviating the dissolution of transition metals in the above-mentioned positive electrode active material comprising the above-mentioned lithium manganese-based oxide and / or the positive electrode prepared using the above-mentioned positive electrode active material is mixed with the above-mentioned lithium manganese-based oxide and used as the positive electrode active material, the lithium-rich lithium manganese-based oxide can also exhibit electrochemical properties and stability at commercializable levels.
[0026] In addition, as mentioned above, the inventors of the present invention have confirmed that when the above-mentioned additive is mixed with the above-mentioned lithium manganese-based oxide and used as a positive electrode active material, compared with the case where the above-mentioned additive is coated on the surface of the above-mentioned lithium manganese-based oxide for use, the gas generation in the lithium secondary battery can be more effectively alleviated under high voltage storage or working environment.
[0027] Therefore, an object of the present invention is to provide a positive electrode active material, which is an additive capable of inhibiting or alleviating the dissolution of transition metals in the positive electrode active material comprising the above-mentioned lithium manganese-based oxide and / or the positive electrode prepared using the above-mentioned positive electrode active material, using a boron-containing compound, and provided in the form of a physical mixture of the above-mentioned lithium manganese-based oxide and the above-mentioned boron-containing compound, thereby being capable of inhibiting or alleviating the dissolution of transition metals and / or impedance anomalies which are the cause of the reduction in the life of the above-mentioned positive electrode active material.
[0028] In addition, another object of the present invention is to provide a positive electrode, which is a positive electrode comprising a positive electrode current collector and a positive electrode active material layer formed on the above-mentioned positive electrode current collector, wherein the above-mentioned positive electrode active material layer contains the positive electrode active material defined in the present invention, a boron-containing compound and a conductive material, thereby being able to effectively inhibit or alleviate the transition metal dissolved from the above-mentioned positive electrode.
[0029] In addition, another object of the present invention is to provide a lithium secondary battery, which can prevent the decrease in rate characteristics and capacity due to the excessive presence of lithium and manganese in the existing OLO by using the positive electrode defined in the present invention, and achieve high stability by reducing the side reaction between the above-mentioned positive electrode active material and the electrolyte, especially in high voltage storage or working environment.
[0030] Solutions to the problem
[0031] According to one aspect of the present invention for solving the above-mentioned technical problems, there is provided a positive electrode active material, which includes a lithium manganese-based oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are solid-dissolved or complexed.
[0032] In the commonly commercialized ternary lithium composite oxides composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA), the phase belonging to the R3-m space group exists as a single phase. However, the lithium-rich lithium manganese-based oxide defined in this article is characterized in that the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group are solid-dissolved or complexed.
[0033] In one embodiment, the positive electrode active material may further include a boron-containing compound. In this case, the boron-containing compound and the lithium manganese-based oxide exist in a physically mixed state.
[0034] The lithium manganese-based oxide, which is one of the components constituting the positive electrode active material, may exist as secondary particles formed by agglomeration of a plurality of primary particles. In this case, the boron-containing compound may exist independently of the secondary particles.
[0035] In addition, at least a portion of the plurality of lithium manganese-based oxides included in the positive electrode active material may be in physical contact with the boron-containing compound.
[0036] In the positive electrode active material, the content of the boron-containing compound may be 0.1 wt % to 3.0 wt %.
[0037] The boron-containing compound may include B2O3, H α B β O γ (0<α<10, 0<β<10, 0<γ<20) and Li α' B β' O γ' At least one of (0<α'<10, 0<β'<10, 0<γ'<20).
[0038] In one embodiment, the lithium manganese-based oxide may be represented by the following Chemical Formula 1.
[0039] [Chemical formula 1]
[0040] Li(Li a M1 x M2 y ) 2-b X b
[0041] (Wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, M2 and M1 are not repeated, X is a halogen that can replace at least a part of the oxygen present in the above-mentioned lithium manganese-based oxide, <a≤0.7,0≤b≤0.1,0<x≤1,0≤y<1,0<x+y≤1)。
[0042] In another embodiment, the lithium manganese-based oxide may be represented by the following Chemical Formula 1-1.
[0043] [Chemical formula 1-1]
[0044] rLi2MnO 3-c X' c ·(1-r)Li a' M1 x' M2 y' O 2-b' X b'
[0045] (Wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, M2 and M1 are not repeated, X and X' are halogens that can replace at least a part of the oxygen present in the above-mentioned lithium manganese-based oxide, <r≤0.7,0≤c≤0.1,0<a'≤1,0≤b'≤0.1,0<x'≤1,0≤y'<1,0<x'+y'≤1)。
[0046] In addition, according to another aspect of the present invention, a positive electrode including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector may be provided, wherein the positive electrode active material layer includes a positive electrode active material defined herein, a boron-containing compound, and a conductive material defined herein.
[0047] The lithium manganese-based oxide and the boron-containing compound may be present in a physically mixed state in the positive electrode active material layer.
[0048] In addition, according to another aspect of the present invention, there is provided a lithium secondary battery, which includes a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte as defined herein.
[0049] Effects of the Invention
[0050] According to the present invention, the limitations of existing lithium-rich lithium manganese-based oxides which are still inferior in electrochemical performance and / or stability compared with commercial ternary lithium composite oxides composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) can be improved.
[0051] Specifically, according to the present invention, by using the lithium manganese-based oxide and the boron-containing compound in a physically mixed manner, the transition metal dissolved from the positive electrode active material containing the lithium manganese-based oxide and / or the positive electrode prepared using the positive electrode active material can be suppressed or alleviated.
[0052] By inhibiting or alleviating the dissolution of transition metals in the positive electrode active material containing the lithium manganese-based oxide and / or the positive electrode prepared using the positive electrode active material, it is possible to prevent the generation of impurities that inhibit normal battery reactions in the lithium secondary battery due to the reaction of the dissolved transition metals with the electrolyte.
[0053] The transition metal dissolved from the lithium manganese-based oxide and / or the impurities formed by the reaction of the dissolved transition metal with the electrolyte may move to the negative electrode with the electrolyte as a medium, and the impurities may be deposited on the surface of the negative electrode, causing the negative electrode resistance to rise sharply. Therefore, as described in the present invention, it is necessary to limit the unintentional movement of transition metals in lithium secondary batteries.
[0054] That is, according to the present invention, by making the lithium manganese-based oxide in the positive electrode active material and the boron-containing compound exist in a physically mixed state, or making the lithium manganese-based oxide in the positive electrode and the boron-containing compound exist in a physically mixed state, the dissolution of transition metals from the positive electrode active material including the lithium manganese-based oxide and / or the positive electrode prepared using the positive electrode active material can be suppressed or mitigated. Therefore, it is possible to prevent the accelerated shortening of the life of the lithium secondary battery due to the deposition of impurities that hinder normal battery reactions on the positive electrode and / or the negative electrode.
[0055] In addition, as described above, the positive electrode active material in which the above-mentioned lithium manganese-based oxide and the above-mentioned boron-containing compound exist in a state of simple physical mixing has the advantage of reducing the gas generation of lithium secondary batteries under high-pressure storage or working environments compared to the positive electrode active material in which the above-mentioned lithium manganese-based oxide and the above-mentioned boron-containing compound form a complex.
[0056] Therefore, by using the cathode defined in this article, the reduction in rate characteristics and capacity due to the excessive presence of lithium and manganese in the existing OLO can be prevented, and in particular, high stability can be achieved by reducing the side reactions between the above-mentioned cathode active material and the electrolyte under storage or working environment at high voltage.
[0057] In addition to the above-described effects, specific effects of the present invention will be described while explaining specific details for implementing the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 is a SEM image of the positive electrode active material prepared according to Example 1.
[0059] Figure 2 : is a cross-sectional SEM image of a positive electrode active material layer prepared using the positive electrode active material prepared according to Example 2. DETAILED DESCRIPTION
[0060] Specific terms are defined herein for ease of understanding. Unless specifically defined herein, scientific terms and technical terms used herein should have the meanings commonly understood by those skilled in the art. In addition, it should be understood that as used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form, and vice versa.
[0061] Hereinafter, a positive electrode active material including a lithium-rich lithium manganese-based oxide and a lithium secondary battery including the positive electrode active material according to the present invention will be described in more detail.
[0062] Positive active material
[0063] According to one aspect of the present invention, there is provided a positive electrode active material, comprising a lithium manganese-based oxide in which a phase belonging to a C2 / m space group and a phase belonging to an R3-m space group are solid-solved or complexed.
[0064] The lithium manganese-based oxide contains at least lithium, nickel and manganese. In this case, in the lithium manganese-based oxide, the content of lithium in the lithium manganese-based oxide is greater than the sum of the contents of other transition metals (the molar ratio of lithium to all metal elements other than lithium in the lithium manganese-based oxide is generally greater than 1), so it is also called overlithiated layered oxide (OLO).
[0065] Generally speaking, considering that the manganese content in the total metal elements other than lithium in the commercial nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) ternary lithium composite oxide is less than 20 mol%, the above-mentioned lithium manganese-based oxide has a relatively high ratio of manganese in the total metal elements compared to the commercial ternary lithium composite oxide (for example, more than 50 mol%, preferably, 55 mol% to 75 mol%).
[0066] Furthermore, considering that the content of nickel in the total metal elements other than lithium in the commercial ternary lithium composite oxide composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) is more than 60 mol % (in the case of high-nickel lithium composite oxide, more than 80 mol %), the above-mentioned lithium manganese-based oxide has a relatively low ratio of nickel in the total metal elements (for example, less than 50 mol %, preferably, 25 mol % to 45 mol %) compared with the commercial ternary lithium composite oxide.
[0067] There is also a difference that the lithium / metal molar ratio measured from the lithium manganese-based oxide defined herein is greater than the lithium / metal molar ratio of a ternary lithium composite oxide such as nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA). For example, the lithium / metal molar ratio of a ternary lithium composite oxide such as nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA) appears to be close to 1. On the other hand, the lithium / metal molar ratio of the lithium manganese-based oxide defined herein is greater than 1, preferably 1.1 to 1.6.
[0068] Despite the above-mentioned difference in composition, the above-mentioned lithium manganese-based oxide can also be used as a composite metal oxide capable of intercalating / deintercalating lithium ions.
[0069] The lithium manganese-based oxide contained in the positive electrode active material defined herein may be present in the form of particles including at least one primary particle.
[0070] When the lithium manganese-based oxide exists as a single primary particle, the lithium manganese-based oxide may be referred to as a single particle. On the other hand, when the lithium manganese-based oxide exists as an aggregate formed by agglomerating a plurality of primary particles, the lithium manganese-based oxide may be referred to as a secondary particle.
[0071] The positive electrode active material may include at least one selected from the group consisting of a lithium manganese-based oxide present as a single particle and a lithium manganese-based oxide present as a secondary particle formed by agglomerating a plurality of primary particles.
[0072] The primary particles constituting the lithium manganese-based oxide may have a rod (bar) shape, an elliptical shape and / or an irregular shape. In addition, unless specifically designed during the manufacturing process, primary particles of various shapes exist in the same positive electrode active material.
[0073] The average particle size of the primary particles constituting the lithium manganese-based oxide defined herein may be 0.05 μm to 5 μm, preferably 0.05 μm to 1.0 μm, more preferably 0.25 μm to 0.75 μm. At this time, as the average particle size of the primary particles, the average value of the length in the major axis direction and the length in the minor axis direction of the primary particles ([major axis length + minor axis length] / 2) may be used.
[0074] When the lithium manganese-based oxide exists as secondary particles formed by aggregation of a plurality of primary particles, the secondary particles may have an average particle size of 0.5 μm to 15 μm. The average particle size of the secondary particles may vary depending on the number of the primary particles constituting the secondary particles.
[0075] Unless otherwise defined, the term "surface of the primary particle" as used herein refers to the outer surface of the primary particle exposed to the outside. Similarly, the term "surface of the secondary particle" as used herein refers to the outer surface of the secondary particle exposed to the outside. In this case, the "surface of the secondary particle" formed by the agglomeration of multiple primary particles is equivalent to the exposed surface of the primary particle existing on the surface of the secondary particle.
[0076] In addition, unless otherwise defined, the term "surface portion of a particle" as used herein refers to an area relatively close to the "surface" of a particle, and the "center portion of a particle" refers to an area relatively close to the "exact center" of a particle compared to the above-mentioned "surface portion". Therefore, the "surface portion of a primary particle" refers to an area relatively close to the "surface" of the above-mentioned primary particle, and the "center portion of a primary particle" refers to an area relatively close to the "exact center" of the above-mentioned primary particle compared to the above-mentioned "surface portion". Similarly, the "surface portion of a secondary particle" refers to an area relatively close to the "surface" of the above-mentioned secondary particle, and the "center portion of a secondary particle" refers to an area relatively close to the "exact center" of the above-mentioned secondary particle compared to the above-mentioned "surface portion".
[0077] At this time, a region other than the “surface portion of the particle” within any particle can be defined as the “center portion of the particle”.
[0078] For example, when the radius of the primary particle is r, the region at a distance of 0 to 0.5r from the surface of the primary particle can be defined as the surface portion of the primary particle, and the region at a distance of 0 to 0.5r from the exact center of the primary particle can be defined as the central portion of the primary particle. If the radius of the primary particle is 0.5 μm, the surface portion of the primary particle can be defined as the region at a distance of 0 to 0.25 μm from the surface of the primary particle, and the central portion of the primary particle can be defined as the region at a distance of 0 to 0.25 μm from the exact center of the primary particle.
[0079] In addition, as needed, when the radius of the above-mentioned primary particle is r, the area at a distance of 0 to 0.1r or 0 to 0.2r from the surface of the above-mentioned primary particle can be defined as the surface part of the above-mentioned primary particle, and the area at a distance of 0 to 0.2r or 0 to 0.5r from the exact center of the above-mentioned primary particle can be defined as the central part of the above-mentioned primary particle.
[0080] Similarly, when the radius of the secondary particle is r, the region at a distance of 0 to 0.5r from the surface of the secondary particle can be defined as the surface portion of the secondary particle, and the region at a distance of 0 to 0.5r from the exact center of the secondary particle can be defined as the central portion of the secondary particle. If the radius of the secondary particle is 2.0 μm, the surface portion of the secondary particle can be defined as the region at a distance of 0 to 1.0 μm from the surface of the secondary particle, and the central portion of the secondary particle can be defined as the region at a distance of 0 to 1.0 μm from the exact center of the secondary particle.
[0081] In addition, as needed, when the radius of the above-mentioned secondary particle is r, the region with a distance of 0 to 0.1r or 0 to 0.2r from the surface of the above-mentioned secondary particle can be defined as the surface portion of the above-mentioned secondary particle, and the region with a distance of 0 to 0.2r or 0 to 0.5r from the exact center of the above-mentioned secondary particle can be defined as the central portion of the above-mentioned secondary particle.
[0082] The above-mentioned lithium manganese-based oxide defined herein may be a lithium-rich lithium manganese-based oxide represented by the following Chemical Formula 1.
[0083] [Chemical formula 1]
[0084] Li(Li a M1 x M2 y ) 2-b X b
[0085] Wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, M2 and M1 are not repeated, X is a halogen capable of replacing at least some of the oxygen present in the above-mentioned lithium manganese-based oxide, and 0 <a≤0.7,0<b≤0.1,0<x≤1,0≤y<1,0<x+y≤1。
[0086] As the kind of halogen that can be used as X, referring to the periodic table, F, Cl, Br and / or I etc. can be used, and preferably F can be used.
[0087] In another embodiment, the lithium manganese-based oxide may be represented by the following Chemical Formula 1-1.
[0088] [Chemical formula 1-1]
[0089] rLi2MnO 3-c X' c ·(1-r)Li a' M1 x' M2 y' O 2-b' X b'
[0090] Wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, M2 and M1 are not repeated, X and X' are halogens capable of replacing at least a portion of the oxygen present in the above-mentioned lithium manganese-based oxide, 0 <r≤0.7,0≤c≤0.1,0<a'≤1,0≤b'≤0.1,0<x'≤1,0≤y'<1,0<x'+y'≤1。
[0091] As the kind of halogen that can be used as X and X', referring to the periodic table, F, Cl, Br and / or I etc. can be used, and preferably, F can be used.
[0092] In the above Chemical Formula 1 and the above Chemical Formula 1-1, when M1 is Ni, M2 may include Mn, and when M1 is Mn, M2 may include Ni. In addition, when M1 is Ni and Mn, M2 may not exist, or, if present, may be an element other than Ni and Mn.
[0093] That is, when M1 is Ni, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd (preferably, at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably, at least one selected from Co, P, B, Si, Ti, Zr and W, and further preferably, at least one selected from P, B and Si) and Mn.
[0094] When M1 is Mn, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd (preferably, at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably, at least one selected from Co, P, B, Si, Ti, Zr and W, further preferably, at least one selected from P, B and Si) and Ni.
[0095] When M1 is Ni and Mn, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, preferably, may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably, may include at least one selected from Co, P, B, Si, Ti, Zr and W, further preferably, may include at least one selected from P, B and Si.
[0096] The lithium manganese-based oxide represented by the above chemical formula 1 or the above chemical formula 1-1 may optionally include cobalt. In addition, when the above lithium manganese-based oxide includes cobalt, the molar number of the above cobalt relative to the molar number of the entire metal element in the above lithium manganese-based oxide may be 20% or less, preferably, 15% or less, and more preferably, 10% or less. In another case, the lithium manganese-based oxide represented by the above chemical formula 1 may have a cobalt-free composition that does not contain cobalt.
[0097] The lithium / metal molar ratio measured from the lithium manganese-based oxide represented by the above chemical formula 1 or the above chemical formula 1-1 may be greater than 1, and preferably, may be 1.1 to 1.6. Only when the lithium / metal molar ratio measured from the above lithium manganese-based oxide is at least greater than 1, can a lithium-rich lithium manganese-based oxide be formed. In addition, in order for the above lithium manganese-based oxide to properly form a solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group in a solid solution or complex, and at the same time exert a high capacity under a high voltage working environment, the lithium / metal molar ratio of the above lithium manganese-based oxide is preferably 1.1 to 1.6.
[0098] In addition, in order to properly form a solid solution or a complex solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group, the manganese content in all metal elements other than lithium present in the lithium manganese-based oxide represented by the above Chemical Formula 1 or the above Chemical Formula 1-1 is preferably 50 mol% or more.
[0099] In order to make the above-mentioned lithium manganese-based oxide have the characteristics of high-capacity OLO under high-voltage working environment, the content of manganese in all metal elements except lithium present in the above-mentioned lithium manganese-based oxide is preferably 50 mol% or more and less than 80 mol%, more preferably 55 mol% to 75 mol%. When the content of manganese in the above-mentioned lithium manganese-based oxide exceeds 80 mol%, a phase change may occur during the formation and / or operation of the lithium secondary battery due to the movement of the transition metal (especially manganese) in the above-mentioned lithium manganese-based oxide. The above-mentioned phase change forms a spinel phase, and the above-mentioned spinel phase acting as an impurity in the above-mentioned lithium manganese-based oxide can cause a decrease in charge / discharge capacity or voltage decay when the lithium secondary battery is cycled.
[0100] In order to properly form a solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group in a solid solution or a complex, the content of nickel among all metal elements other than lithium present in the lithium manganese-based oxide represented by the above Chemical Formula 1 or the above Chemical Formula 1-1 is preferably less than 50 mol%.
[0101] When the nickel content in the above-mentioned lithium manganese-based oxide is above 50 mol%, it is difficult to fully form the C2 / m phase, or the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group may not form a sufficient solid solution, resulting in phase separation during the formation and / or operation of the lithium secondary battery.
[0102] Generally, in a commercially available ternary lithium composite oxide composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA), a phase belonging to the R3-m space group exists as a single phase.
[0103] On the other hand, the lithium-rich lithium manganese-based oxide represented by the above Chemical Formula 1 or the above Chemical Formula 1-1 is an oxide of a phase belonging to the C2 / m space group represented by rLi2MnO3 (hereinafter referred to as "C2 / m phase") and a phase represented by (1-r)Li a M1 x M2 y O 2- b X b The present invention provides a composite oxide formed by solid solution or complexation of an oxide belonging to a phase of the R3-m space group (hereinafter referred to as "R3-m phase"). For example, the lithium manganese-based oxide may exist in a state where an oxide of the C2 / m phase and an oxide of the R3-m phase form a solid solution.
[0104] In this case, a composite oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are simply physically and / or chemically bonded or combined does not correspond to a solid solution as defined herein.
[0105] For example, a composite oxide having a phase belonging to the C2 / m space group whose surface is coated with a metal oxide belonging to the R3-m space group by mixing a metal oxide having a phase belonging to the C2 / m space group and a metal oxide having a phase belonging to the R3-m space group does not correspond to the solid solution defined in this article.
[0106] In the lithium manganese-based oxide represented by the above chemical formula 1-1, when r exceeds 0.7, the ratio of Li2MnO3 as the oxide of the C2 / m phase in the above lithium manganese-based oxide is excessively increased, which may lead to an excessive increase in the manganese content in the positive electrode active material and a decrease in discharge capacity. That is, in order to fully activate the C2 / m phase oxide with relatively high resistance in the above lithium manganese-based oxide to improve the surface dynamics, the R3-m phase oxide is preferably present at a predetermined ratio or more.
[0107] In one embodiment, the positive electrode active material may further include a boron-containing compound. In this case, the boron-containing compound and the lithium manganese-based oxide exist in a physically mixed state.
[0108] The existence of the lithium manganese-based oxide and the boron-containing compound in a physically mixed state does not mean that the lithium manganese-based oxide and the boron-containing compound form a complex, but means that the lithium manganese-based oxide and the boron-containing compound exist in the form of independent particles.
[0109] Here, the state in which the lithium manganese-based oxide and the boron-containing compound are physically mixed should be distinguished from the state in which the surface of the lithium manganese-based oxide is coated with the boron-containing compound in the form of an oxide.
[0110] That is to say, the above-mentioned lithium manganese-based oxide and the above-mentioned boron-containing compound exist in a physically mixed state, which means that when the above-mentioned lithium manganese-based oxide, which is one of the components constituting the above-mentioned positive electrode active material, exists as secondary particles formed by the aggregation of multiple primary particles, the above-mentioned boron-containing compound exists independently of the above-mentioned primary particles and / or the above-mentioned secondary particles.
[0111] At this time, at least a portion of the multiple lithium manganese-based oxides contained in the above-mentioned positive electrode active material may be in physical contact with the above-mentioned boron-containing compound, but such physical contact state is different from the case where the above-mentioned boron-containing compound is inseparably coated on the surface of the above-mentioned lithium manganese-based oxide.
[0112] The average particle size of the boron-containing compound in the positive electrode active material can be 50nm to 80μm, preferably, 50nm to 60μm, and more preferably, 50nm to 30μm. At this time, as the average particle size of the boron-containing compound, the average value of the length in the major axis direction and the length in the minor axis direction of the boron-containing compound can be used ([major axis length-axis length] / 2), or D50 according to the particle size distribution analysis of the boron-containing compound can also be used.
[0113] When the average particle size of the boron-containing compound is less than 50 nm, the dispersibility of the boron-containing compound in the positive electrode slurry including the positive electrode active material physically mixed with the lithium manganese-based oxide and the boron-containing compound is low, and uniform control may be difficult to achieve.
[0114] On the contrary, when the average particle size of the above-mentioned boron-containing compound is greater than 80μm, or the proportion of particles with a particle size greater than 80μm in the above-mentioned boron-containing compound exceeds 50wt%, it may be difficult to use the above-mentioned positive electrode active material in which the above-mentioned lithium manganese-based oxide is physically mixed with the above-mentioned boron-containing compound to prepare a positive electrode active material layer.
[0115] The content of the boron-containing compound in the positive electrode active material may be 0.1 wt % to 3.0 wt %, preferably 0.1 wt % to 2.0 wt %, and more preferably 0.3 wt % to 1.5 wt %.
[0116] When the content of the boron-containing compound is less than 0.1 wt % based on the total weight of the positive electrode active material, it is difficult to fully inhibit or alleviate the dissolution of transition metals in the positive electrode active material comprising the lithium manganese-based oxide and / or the positive electrode prepared using the positive electrode active material.
[0117] On the contrary, when the content of the boron-containing compound exceeds 3.0% by weight based on the total weight of the positive active material, the lithium secondary battery using the positive active material may have insufficient capacity due to the reduction in the proportion of the lithium manganese-based oxide in the total weight of the positive active material. In addition, as the relative content of the boron-containing compound in the positive active material increases, the impedance of the positive active material may increase unnecessarily.
[0118] The boron-containing compound may include B2O3, H α B β O γ (0<α<10, 0<β<10, 0<γ<20) and Li α' B β' O γ'At least one of (0<α'<10, 0<β'<10, 0<γ'<20). In addition, the boron-containing compound can be mutually converted in a lithium secondary battery using the positive electrode active material.
[0119] Lithium secondary battery
[0120] According to another aspect of the present invention, a positive electrode including a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector may be provided.
[0121] Here, the positive electrode active material layer may include a positive electrode active material including a lithium manganese-based oxide, a boron-containing compound and a conductive material as defined in the present application. When the positive electrode active material layer includes a boron-containing compound independently of the positive electrode active material, the positive electrode active material may not include a boron-containing compound.
[0122] In one embodiment, the boron-containing compound in the positive electrode active material layer exists in a state of being physically mixed with the lithium manganese-based oxide.
[0123] The existence of the lithium manganese-based oxide and the boron-containing compound in a physically mixed state does not mean that the lithium manganese-based oxide and the boron-containing compound form a complex, but means that the lithium manganese-based oxide and the boron-containing compound exist in the form of independent particles.
[0124] Here, the state in which the lithium manganese-based oxide and the boron-containing compound are physically mixed should be distinguished from the state in which the surface of the lithium manganese-based oxide is coated with the boron-containing compound in the form of an oxide.
[0125] At this time, at least a portion of the multiple lithium manganese-based oxides contained in the above-mentioned positive electrode active material may be in physical contact with the above-mentioned boron-containing compound, but such physical contact state is different from the case where the above-mentioned boron-containing compound is inseparably coated on the surface of the above-mentioned lithium manganese-based oxide.
[0126] The average particle size of the boron-containing compound in the positive electrode active material can be 50nm to 60μm, preferably, 50nm to 30μm, and more preferably, 50nm to 15μm. At this time, as the average particle size of the boron-containing compound, the average value of the length in the major axis direction and the length in the minor axis direction of the boron-containing compound ([major axis length / minor axis length] / 2) can be used, or D50 according to the particle size distribution analysis of the boron-containing compound can be used.
[0127] When the average particle size of the boron-containing compound in the positive electrode active material layer is less than 50 nm, the boron-containing compound is less likely to be uniformly dispersed in the positive electrode active material layer.
[0128] On the other hand, if the average particle size of the boron-containing compound in the positive electrode active material layer is greater than 60 μm or the proportion of particles with a particle size of 60 μm or more in the boron-containing compound exceeds 50% by weight, the boron-containing compound may be difficult to dissolve in the electrolyte. During the storage and / or operation of the lithium secondary battery, the boron-containing compound present in the positive electrode active material or the positive electrode active material layer may be dissolved in the electrolyte, and the boron-containing compound dissolved in the electrolyte may form a physical barrier layer on the positive electrode surface, inhibiting or alleviating the dissolution of transition metals from the positive electrode.
[0129] In addition, the boron-containing compound dissolved in the electrolyte can move to the negative electrode and form a physical barrier layer on the surface of the negative electrode. As described above, the physical barrier layer formed on the surface of the negative electrode can prevent the transition metal dissolved from the lithium manganese-based oxide and / or impurities caused by the dissolved transition metal from being deposited on the surface of the negative electrode.
[0130] The physical barrier layer may include a boron-containing oxide represented by Chemical Formula 2 below.
[0131] [Chemical formula 2]
[0132] Li c B d M3 e O f
[0133] Wherein, M3 is at least one selected from Ni, Mn, Co, Al, Nb, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, 0≤c≤8, 0 <d≤8,0≤e≤8,2≤f≤13。
[0134] The boron-containing oxide represented by the above chemical formula 2 is a borate-based compound or an LBO (lithium borate)-based compound. Non-limiting examples of the above boron-containing oxide include B2O3, Li2O-B2O3, Li3BO3, Li2B4O7, Li2B2O7, Li2B8O 13 Etc. In addition, the boron-containing oxide may have a composition in which M3 as a different element is selectively doped into the borate-based compound or the lithium borate-based compound.
[0135] The content of the boron-containing compound in the positive electrode active material layer may be 0.09 wt % to 3.0 wt %, and preferably 0.09 wt % to 2.0 wt %.
[0136] When the content of the above-mentioned boron-containing compound is less than 0.09 weight % based on the total weight of the solid matter in the above-mentioned positive electrode active material layer, it may be difficult to fully inhibit or reduce the dissolution of transition metals from the above-mentioned positive electrode. In addition, as the amount of the above-mentioned boron-containing compound dissolved in the above-mentioned electrolyte decreases, during the storage and / or operation of the above-mentioned lithium secondary battery, it may be difficult to fully form a physical barrier layer on the surface of the above-mentioned positive electrode and / or the above-mentioned negative electrode.
[0137] On the other hand, when the content of the boron-containing compound exceeds 3.0% by weight based on the total weight of the positive electrode active material, the capacity of the lithium secondary battery using the positive electrode active material may become insufficient due to the decrease in the ratio of the lithium manganese-based oxide to the total weight of the positive electrode active material. In addition, as the relative content of the boron-containing compound in the positive electrode active material increases, the impedance of the positive electrode active material may be unnecessarily increased.
[0138] The boron-containing compound may include B2O3, H α B β O γ (0<α<10, 0<β<10, 0<γ<20) and Li α' B β' O γ' At least one of (0<α'<10, 0<β'<10, 0<γ'<20). In addition, the boron-containing compound can be mutually converted in a lithium secondary battery using the positive electrode active material.
[0139] As long as the positive electrode current collector does not induce chemical changes in the battery and has conductivity, there is no particular restriction. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or the surface of aluminum or stainless steel may be treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine concavoconvexities may be formed on the surface of the current collector to improve the bonding force of the positive electrode active material. For example, it may be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a non-woven body.
[0140] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition including the positive electrode active material, a conductive material, and optionally a binder as required, on the positive electrode current collector.
[0141] At this time, the content of the positive electrode active material can be 80 wt % to 99 wt %, more specifically 85 wt % to 98.5 wt % relative to the total weight of the positive electrode active material layer. When the positive electrode active material is included in the above content range, excellent capacity performance can be shown, but it is not limited thereto.
[0142] The above-mentioned conductive materials are used to impart conductivity to the electrode. In the battery formed, as long as they do not cause chemical changes and have electronic conductivity, they can be used without limitation. As specific examples, graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, etc., and one of them or a mixture of two or more thereof can be used. The above-mentioned conductive material may be included in an amount of 0.1% to 15% by weight relative to the total weight of the positive electrode active material layer.
[0143] The above-mentioned binder serves to improve the adhesion between multiple positive electrode active material particles and the bonding force between the positive electrode active material and the current collector. As a specific example, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated ethylene propylene diene rubber, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, etc., can be used. One or a mixture of two or more thereof. Relative to the total weight of the positive electrode active material layer, 0.1 wt % to 15 wt % of the above-mentioned binder may be included.
[0144] In addition to using the above-mentioned positive electrode active material, the above-mentioned positive electrode can be prepared according to a common positive electrode preparation method. Specifically, it can be prepared by coating a positive electrode slurry composition on a positive electrode current collector and then drying and rolling it. The above-mentioned positive electrode slurry composition is prepared by dissolving or dispersing the above-mentioned positive electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent.
[0145] The above-mentioned solvent can be a solvent commonly used in the technical field, and examples thereof include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone or water, and a mixture of one or more of them can be used. Considering the coating thickness and preparation yield of the slurry, the amount of the above-mentioned solvent used is as long as it can dissolve or disperse the above-mentioned positive electrode active material, conductive material and binder and has a viscosity that can show excellent thickness uniformity when applied for preparing the positive electrode.
[0146] Furthermore, in another embodiment, the positive electrode may be prepared by casting the positive electrode slurry composition on a separate support, and then laminating a thin film obtained by peeling the support on a positive electrode current collector.
[0147] In addition, according to another aspect of the present invention, an electrochemical device comprising the positive electrode described above can be provided. Specifically, the electrochemical device described above can be a battery, a capacitor, etc., and more specifically, can be a lithium secondary battery.
[0148] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, and a separator and an electrolyte disposed between the positive electrode and the negative electrode. The positive electrode is the same as described above, so for convenience, the specific description is omitted, and only the remaining components not described above are described below.
[0149] The lithium secondary battery may further include: a battery container for accommodating the electrode assembly of the positive electrode, the negative electrode and the separator; and a sealing member for sealing the battery container.
[0150] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0151] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector can usually have a thickness of 3μm to 500μm. Similar to the positive electrode current collector, the binding force of the negative electrode active material can be strengthened by forming fine concave and convex on the surface of the current collector. For example, it can be used in various forms such as thin film, sheet, foil, net, porous body, foam, non-woven body, etc.
[0152] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition including the negative electrode active material and a conductive material and optionally including a binder as required on the negative electrode current collector.
[0153] As the negative electrode active material, a compound capable of reversibly inserting and extracting lithium can be used. Specific examples include carbon materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; such as SiO β(0<β<2), SnO2, vanadium oxide, lithium vanadium oxide, metal oxides capable of being doped and dedoped with lithium; or composites containing the above metal compounds and carbon materials such as Si-C composites or Sn-C composites, etc., and one or a mixture of two or more of them can be used. In addition, as the above-mentioned negative electrode active material, a metal lithium film can also be used. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Representative low-crystalline carbons are soft carbon and hard carbon, and representative high-crystalline carbons are amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, Kishgraphite, pyrolytic carbon, mesophase pitch based carbon fiber, mesophase carbon microbeads, mesophase pitch, and high-temperature calcined carbons such as petroleum or coal tar pitch derived cokes.
[0154] The negative electrode active material layer may contain 80 wt % to 99 wt % of the negative electrode active material, based on the total weight of the negative electrode active material layer.
[0155] The binder is a component that helps to bind the conductive material, the active material and the current collector. Usually, based on the total weight of the negative electrode active material layer, 0.1 wt % to 10 wt % of the binder can be added. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber, sulfonated ethylene propylene diene rubber, styrene butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof.
[0156] The conductive material is a component used to further improve the conductivity of the negative electrode active material. Based on the total weight of the negative electrode active material layer, the conductive material can be added in an amount of 10% by weight or less, preferably 5% by weight or less. There are no particular restrictions on such conductive materials as long as they do not induce chemical changes in the corresponding battery and have conductivity. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. can be used.
[0157] In one embodiment, the negative electrode active material layer can be prepared by coating a negative electrode slurry composition on a negative electrode current collector and drying it, wherein the negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent, or by casting the negative electrode slurry composition on a separate support and laminating a thin film obtained by peeling off the support on the negative electrode current collector.
[0158] On the other hand, in the above-mentioned lithium secondary battery, the diaphragm is used to separate the negative electrode and the positive electrode and provide a mobile channel for lithium ions. As long as the diaphragm commonly used in the lithium secondary battery, it can be used without restriction, especially, preferably, for the ion movement of the electrolyte, the impedance is low and there is excellent electrolyte moisture-containing capacity. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers or their two or more layers of stacked structures. In addition, a common porous non-woven fabric can also be used, for example, a non-woven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, in order to ensure heat resistance or mechanical strength, a diaphragm coated with a ceramic component and a polymer substance can also be used, and it can be selectively used with a single layer or multilayer structure.
[0159] Furthermore, examples of the electrolyte used in the present invention include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in preparing lithium secondary batteries.
[0160] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0161] As the above-mentioned organic solvent, any organic solvent that can act as a medium for the movement of ions involved in the electrochemical reaction of the battery can be used without limitation. Specifically, as the above-mentioned organic solvent, ester solvents such as methylacetate, ethylacetate, γ-butyrolactone, ε-caprolactone, etc.; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (propylene carbonate) and the like can be used. carbonate, PC) and other carbonate solvents; alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (r is a straight-chain, branched or cyclic hydrocarbon group with 2 to 20 carbon atoms, which may contain a double-bonded aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolane, etc. Among them, carbonate solvents are preferred, and more preferably, a mixture of cyclic carbonates (such as ethylene carbonate or propylene carbonate) with high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery, and low-viscosity linear carbonate compounds (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate, etc.). In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, excellent electrolyte performance can be shown.
[0162] The above-mentioned lithium salt can be used without limitation as a compound that can provide lithium ions used in a lithium secondary battery. Specifically, the above-mentioned lithium salt can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2, etc. Preferably, the concentration of the above-mentioned lithium salt is used in the range of 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore, excellent electrolyte performance can be shown, and lithium ions can be effectively moved.
[0163] When the electrolyte used herein is a solid electrolyte, for example, a solid inorganic electrolyte such as a sulfide solid electrolyte, an oxide solid electrolyte, a nitride solid electrolyte, or a halide solid electrolyte can be used, and preferably a sulfide solid electrolyte can be used.
[0164] As the material of the sulfide solid electrolyte, a solid electrolyte containing Li, an X element (wherein X is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga and In) and S can be used. Examples of the above-mentioned sulfide solid electrolyte materials include Li2S-P2S5, Li2S-P2S-LiX (wherein X is a halogen element such as I or Cl), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are integers, Z is Ge, Zn or Gam), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (wherein p and q are integers, and M is P, Si, Ge, B, Al, Ga or In), etc.
[0165] The solid electrolyte, preferably a sulfide-based solid electrolyte, may be in an amorphous state, a crystalline state, or a mixed state of the amorphous state and the crystalline state.
[0166] Examples of materials for oxide-based solid electrolytes include Li7La3Zr2O 12 , Li 7-x Ln3Z1-x Nb x O 12 , Li 7- 3x La3Zr2Al x O 12 , Li 3x La 2 / 3-x TiO3、Li 1+x Al x Ti 2-x (PO4)3、Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, Li 3+x PO 4-x N x (LiPON), Li 2+2x Zn 1-x GeO4(LISICON), etc.
[0167] The solid electrolyte may be arranged between the positive electrode and the negative electrode as a separate layer (solid electrolyte layer). In addition, the solid electrolyte may be partially contained in the positive electrode active material layer of the positive electrode independently of the solid electrolyte layer, or the solid electrolyte may be partially contained in the negative electrode active material layer of the negative electrode independently of the solid electrolyte layer.
[0168] In addition to the above electrolyte components, the electrolyte may further include one or more additives such as halogenated alkylene carbonate compounds such as bisfluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, etc., for the purpose of improving the life characteristics of the battery, inhibiting the reduction of the battery capacity, and increasing the discharge capacity of the battery. In this case, the above additives may be included in an amount of 0.1 wt % to 5 wt % relative to the total weight of the electrolyte.
[0169] As described above, the lithium secondary battery containing the positive electrode active material of the present invention stably shows excellent discharge capacity, output characteristics and life characteristics, and can therefore be used in portable devices such as mobile phones, notebook computers, digital cameras, and electric vehicles such as hybrid electric vehicles (HEV).
[0170] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a prismatic shape, a pouch shape, a coin shape, etc. Also, preferably, the lithium secondary battery can be used not only as a battery cell used as a power source for small devices, but also as a unit battery of a medium or large battery module including a plurality of battery cells.
[0171] According to another aspect of the present invention, a battery module including the above-mentioned lithium secondary battery as a unit cell and / or a battery pack including the same may be provided.
[0172] The battery module or the battery pack can be used as a power tool; an electric vehicle including an electric vehicle (EV), a hybrid electric vehicle and a plug-in hybrid electric vehicle (PHEV); or a power source for one or more medium or large devices in a power storage system.
[0173] Hereinafter, the present invention will be described in more detail by way of examples. However, these examples are only for illustrating the present invention, and the scope of the present invention should not be construed as being limited by these examples.
[0174] Manufacturing Example 1. Preparation of positive electrode active material
[0175] Example 1
[0176] (a) Precursor preparation
[0177] An aqueous solution of NiSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:60, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 45°C, and the precursor synthesis reaction was carried out while N2 gas was introduced into the reactor. After the reaction was completed, the Ni was washed and dehydrated to obtain a Ni 0.4 Mn 0.6 (OH)2 precursor.
[0178] (b) Precursor coating
[0179] In the reactor in which the precursor obtained in step (a) is stirred, an aqueous solution of NiSO4·6H2O, NaOH and NH4OH are added. At this time, NiSO4·6H2O is weighed to 5 mol% and then added. After the reaction is completed, washing and dehydration are performed, and then drying is performed at 150° C. for 14 hours to obtain a coated precursor.
[0180] (c) First heat treatment
[0181] The sintering furnace in an air atmosphere was heated at a rate of 2° C. / min, and then the precursor obtained in step (b) was heat-treated for 5 hours while maintaining 550° C., followed by furnace cooling to obtain a precursor in an oxide state.
[0182] (d) Second heat treatment
[0183] A mixture was prepared by mixing the precursor in an oxide state obtained in step (c) with LiOH (molar ratio of lithium / (metal other than lithium) = 1.22) as a lithium raw material material.
[0184] Next, the sintering furnace in an O2 atmosphere was heated at a rate of 2°C / min, and then the mixture was heat-treated for 8 hours while maintaining 900°C, and then furnace-cooled to obtain a lithium-rich lithium manganese-based oxide.
[0185] As a result of TEM / EDS analysis of the above-mentioned lithium manganese-based oxide, it can be confirmed that by applying the nickel precursor in the above-mentioned step (b), a gradient is formed in which the nickel concentration increases from the center toward the surface and the manganese concentration decreases from the center toward the surface.
[0186] (e) Mixed with boron-containing compounds
[0187] The lithium manganese-based oxide obtained in step (d) and B2O3 having an average particle size of 40 μm as a boron-containing compound are mixed to obtain a final product of a physical mixture of the lithium manganese-based oxide and the boron-containing compound. At this time, the mixing amount of the boron-containing compound is 0.3% by weight based on the total weight of the final product.
[0188] Example 2
[0189] A positive electrode active material was prepared in the same manner as in Example 1, except that the mixing amount of the boron-containing compound was 0.7 wt % based on the total weight of the final product.
[0190] Example 3
[0191] A positive electrode active material was prepared in the same manner as in Example 1, except that the mixing amount of the boron-containing compound was 1.5 wt % based on the total weight of the final product.
[0192] Comparative Example 1
[0193] A positive electrode active material was prepared in the same manner as in Example 1 except that step (e) was not performed.
[0194] Reference Example 1
[0195] A positive electrode active material was prepared in the same manner as in Example 1, except that in the above step (e), the mixing amount of B2O3 having an average particle size of 100 μm was 0.7 wt % based on the total weight of the final product.
[0196] Reference Example 2
[0197] A positive electrode active material was prepared in the same manner as in Example 1, except that the mixing amount of the boron-containing compound was 0.05 wt % based on the total weight of the final product.
[0198] Manufacturing Example 2. Manufacturing of a lithium secondary battery (half-cell)
[0199] 90 wt % of each positive electrode active material prepared according to Examples 1 to 3, Comparative Example 1 and Reference Examples 1 to 2 described in Manufacturing Example 1, 4.5 wt % of carbon black and 5.5 wt % of PVDF binder were dispersed in N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry.
[0200] The positive electrode slurry was uniformly coated on an aluminum thin film with a thickness of 15 μm, and vacuum dried at 135° C., thereby preparing a positive electrode for a lithium secondary battery having a positive electrode active material layer formed thereon.
[0201] Relative to the above-mentioned positive electrode, lithium foil is used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) is used as a separator, and an electrolyte containing LiPF6 at a concentration of 1.15 M in a solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate mixed in a volume ratio of 2:4:4 is used to prepare a half-cell.
[0202] At this time, when the positive electrode active material prepared according to Reference Example 1 was used, since the average particle size of B2O3 was too large, scratches occurred on the surface of the positive electrode active material layer, and a normal positive electrode active material layer could not be formed.
[0203] Manufacturing Example 3. Manufacturing of a lithium secondary battery (half-cell)
[0204] 90 wt % of the positive electrode active material prepared in Comparative Example 1 described in Manufacturing Example 1, 4.5 wt % of carbon black, 5.5 wt % of PVDF binder, and B2O3 having an average particle size of 40 μm as a boron-containing compound were dispersed in N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. Here, the mixing amount of the boron-containing compound is 0.6 wt % relative to the total weight of the solid matter in the positive electrode slurry.
[0205] The positive electrode slurry was uniformly coated on an aluminum thin film with a thickness of 15 μm, and vacuum dried at 135° C., thereby preparing a positive electrode for a lithium secondary battery having a positive electrode active material layer formed thereon.
[0206] Relative to the above-mentioned positive electrode, lithium foil is used as the counter electrode, a porous polyethylene film (Celgard2300, thickness: 25μm) is used as a separator, and an electrolyte containing LiPF6 at a concentration of 1.15M in a solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate mixed in a volume ratio of 2:4:4 is used to prepare a half-cell.
[0207] Manufacturing Example 4. Manufacturing of lithium secondary battery (full battery)
[0208] 90 wt % of the positive electrode active material prepared according to Examples 1 to 3, Comparative Example 1 and Reference Examples 1 to 2 described in Manufacturing Example 1, 4.5 wt % of carbon black and 5.5 wt % of PVDF binder were dispersed in N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry.
[0209] The positive electrode slurry was uniformly coated on an aluminum thin film with a thickness of 15 μm, and vacuum dried at 135° C., thereby preparing a positive electrode for a lithium secondary battery having a positive electrode active material layer formed thereon.
[0210] Relative to the above-mentioned positive electrode, a graphite electrode is used as a counter electrode, a porous polyethylene film (Cel gard 2300, thickness: 25 μm) is used as a separator, and a full battery is prepared using an electrolyte solution in which LiPF6 is present at a concentration of 1.15 M in a solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate mixed in a volume ratio of 2:4:4.
[0211] At this time, when the positive electrode active material prepared according to Reference Example 1 was used, since the average particle size of B2O3 was too large, scratches occurred on the surface of the positive electrode active material layer, and a normal positive electrode active material layer could not be formed.
[0212] Manufacturing Example 5. Manufacturing of a lithium secondary battery (full battery)
[0213] 90 wt % of the positive electrode active material prepared according to Comparative Example 1 described in Manufacturing Example 1, 4.5 wt % of carbon black, 5.5 wt % of PVDF binder and B2O3 having an average particle size of 40 μm as a boron-containing compound were dispersed in N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. Here, the mixing amount of the boron-containing compound is 0.6 wt % relative to the total weight of the solid matter in the above-mentioned positive electrode slurry.
[0214] The positive electrode slurry was uniformly coated on an aluminum thin film with a thickness of 15 μm, and vacuum dried at 135° C., thereby preparing a positive electrode for a lithium secondary battery having a positive electrode active material layer formed thereon.
[0215] Relative to the above-mentioned positive electrode, a graphite electrode is used as a counter electrode, a porous polyethylene film (Cel gard 2300, thickness: 25 μm) is used as a separator, and a full battery is prepared using an electrolyte solution in which LiPF6 is present at a concentration of 1.15 M in a solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate mixed in a volume ratio of 2:4:4.
[0216] Experimental Example 1. SEM analysis of positive electrode active material
[0217] Figure 1 is a SEM image of the positive electrode active material prepared according to Example 1.
[0218] Reference Figure 1 It can be confirmed that the lithium manganese-based oxide and the boron-containing compound in the form of secondary particles coexist in the positive electrode active material. In other words, it can be confirmed that the lithium manganese-based oxide in the positive electrode active material exists in the form of secondary particles formed by agglomeration of multiple primary particles, and the boron-containing compound exists independently of the secondary particles.
[0219] Furthermore, it was confirmed that at least a part of the plurality of lithium manganese-based oxides contained in the positive electrode active material was present in a state of being in physical contact with the boron-containing compound.
[0220] Experimental Example 2. SEM analysis of positive electrode cross section
[0221] The distribution of lithium manganese-based oxide and boron-containing compound in the positive electrode active material layer was analyzed by cross-sectional SEM image analysis of the positive electrode active material layer prepared according to the positive electrode active material prepared in Example 2 of Manufacturing Example 2. At this time, the positive electrode active material layer was analyzed after the positive electrode was manufactured according to the method described in Manufacturing Example 2 and before being assembled into a half-cell. The above analysis results are as follows: Figure 2 shown.
[0222] Reference Figure 2 It can be confirmed that the boron element in the positive electrode active material layer is uniformly distributed as a whole and Figure 1 Compared with the boron-containing compounds confirmed in the literature, the particle size of the boron-containing compounds is reduced to tens to hundreds of nanometers.
[0223] The above results are expected to be caused by the partial dissolution of the boron-containing compound in the solvent during the positive electrode manufacturing process. Therefore, the boron-containing compound in the positive electrode active material layer may be in a state of overall dispersion. Figure 2 As a result, it can be confirmed that during the positive electrode manufacturing process, the boron-containing compound partially dissolved in the solvent or the like may be converted into a physical barrier layer on the surface of the positive electrode active material layer.
[0224] Experimental Example 3. Dissolution Analysis of Boron-Containing Compounds
[0225] The positive electrode produced using the positive electrode active material prepared according to Example 2 in Production Example 2 and the positive electrode produced in Production Example 3 were stored in an electrolyte at 60° C. for 3 days and then recovered, and the boron content in the positive electrode was measured by ICP analysis. The above measurement results are shown in Table 1 below.
[0226] Table 1
[0227] Classification Boron content before storage (ppm) Boron content after storage (ppm) Production Example 2 (Example 2) 1646 61 Production Example 3 1740 24
[0228] Referring to the results in Table 1 above, it can be confirmed that when the positive electrode manufactured using the positive electrode active material prepared according to Example 2 in Manufacturing Example 2 and the positive electrode manufactured in Manufacturing Example 3 are stored in an electrolyte at a relatively high temperature, the boron-containing compound present in the above positive electrode dissolves, resulting in a decrease in the content of the boron-containing compound in the above positive electrode.
[0229] As described above, the boron-containing compound in the positive electrode may be dissolved in the electrolyte, and the boron-containing compound dissolved in the electrolyte may be converted into a physical barrier layer on the surface of the positive electrode active material layer and / or the negative electrode active material layer.
[0230] Experimental Example 4. Evaluation of electrochemical characteristics of lithium secondary battery (half-cell)
[0231] For the lithium secondary batteries (half-cells) manufactured in Manufacturing Example 2 and Manufacturing Example 3, an electrochemical analyzer (Toyo, Toscat-3100) was used to measure the initial charge capacity, initial discharge capacity, initial reversible efficiency and rate characteristics (discharge capacity ratio; rate capability (rate capability, C-rate)) by conducting a charge / discharge experiment at 25°C, a voltage range of 2.0V to 4.6V and a discharge rate of 0.1C, 1.0C and 2.0C.
[0232] The above measurement results are shown in Table 2 below.
[0233] Table 2
[0234]
[0235] Referring to the half-cell evaluation results in Table 2 above, it can be confirmed that even if a boron-containing compound is physically mixed in the positive electrode active material or the positive electrode active material layer, its initial charge capacity, initial discharge capacity, initial reversible efficiency and rate characteristics are not reduced, and in particular, some indicators (for example, initial efficiency and discharge capacity) are even improved.
[0236] Experimental Example 5. Evaluation of electrochemical characteristics of lithium secondary battery (full battery)
[0237] For the lithium secondary batteries (full batteries) manufactured in Manufacturing Examples 4 and 5, an electrochemical analyzer (Toyo, Toscat-3100) was used to complete 6 cycles of formation at 25°C, a voltage range of 2.0V to 4.6V, and 0.2C / 0.2C, and then charged / discharged 500 times at 25°C, a voltage range of 2.0V to 4.6V, and 1C / 1C. The initial (first cycle) discharge capacity and the ratio of the discharge capacity at the 500th cycle relative to the initial discharge capacity (cycle capacity retention; capacity retention) were measured.
[0238] The above measurement results are shown in Table 3 below.
[0239] Table 3
[0240]
[0241]
[0242] Referring to the full battery evaluation results in Table 3 above, it can be confirmed that, unlike the half-battery evaluation results in Table 2, the full battery using the positive electrode active material according to Examples 1 to 3 exhibits a significantly higher cycle capacity retention rate than the full battery using the positive electrode active material according to Comparative Example 1. The above results are expected to be because the full battery using the positive electrode active material according to Comparative Example 1 has an impedance anomaly at the negative electrode due to the dissolution of the transition metal in the lithium manganese-based oxide, which accelerates the shortening of the life.
[0243] On the other hand, the full battery of Reference Example 2 has a higher cycle capacity retention rate than the full battery using the positive electrode active material according to Comparative Example 1, but due to the lower content of boron-containing compounds physically mixed with the lithium manganese-based oxide, its life degradation degree is still higher than that of the full battery using the positive electrode active material according to Examples 1 to 3.
[0244] In addition, the full battery according to Preparation Example 5, which used the positive electrode active material according to Comparative Example 1 but physically mixed the boron-containing compound during the positive electrode manufacturing process, also showed a cycle capacity retention rate at a level similar to that of Example 1.
[0245] Experimental Example 6. Dissolution analysis of transition metals
[0246] For the lithium secondary battery (full battery) manufactured according to the positive electrode active material prepared in Example 2 and Comparative Example 1 in Manufacturing Example 4 and the lithium secondary battery (full battery) manufactured in Manufacturing Example 5, an electrochemical analysis device (Toyo, Toscat-3100) was used to complete 6 cycles of formation at 25°C, a voltage range of 2.0V to 4.6V, and 0.2C / 0.2C, and then 2 cycles of charge / discharge were performed at 25°C, a voltage range of 2.0V to 4.6V, and 0.05C / 0.05C to stabilize. Then, after the full battery was disassembled, the negative electrode was cleaned with a diethyl carbonate solvent, vacuum dried at 60°C, and then recovered.
[0247] Only the negative electrode active material was separated from the recovered copper foil (current collector) of the negative electrode, and the separated negative electrode active material was subjected to ICP analysis to measure the contents of nickel, manganese, and boron contained in the negative electrode active material.
[0248] In addition, for the lithium secondary battery (full battery) manufactured using the positive electrode active material prepared according to Example 2 and Comparative Example 1 in Manufacturing Example 4 and the lithium secondary battery (full battery) manufactured in Manufacturing Example 5, an electrochemical analysis device (Toyo, Toscat-3100) was used to complete 6 cycles of formation at 25°C, a voltage range of 2.0V to 4.6V, and 0.2C / 0.2C, and then 500 cycles of charge / discharge were performed at 25°C, a voltage range of 2.0V to 4.6V, and 1C / 1C. Subsequently, the battery was stabilized by performing secondary cycle charge / discharge at 25°C, a voltage range of 2.0V to 4.6V, and 0.05C / 0.05C. Then, after the full battery was disassembled, the negative electrode was cleaned with a diethyl carbonate solvent, vacuum dried at 60°C, and then recovered.
[0249] Only the negative electrode active material was separated from the recovered copper foil (current collector) of the recovered negative electrode, and the contents of nickel, manganese, and boron contained in the negative electrode active material were measured by ICP analysis of the separated negative electrode active material.
[0250] The above measurement results are shown in Table 4 below.
[0251] Table 4
[0252]
[0253] Referring to the results in Table 4 above, it can be confirmed that, as expected in Experimental Example 5, the rapid life degradation of the full battery using the positive electrode active material according to Comparative Example 1 is caused by the relative increase in the content of transition metals deposited on the negative electrode active material as charge and discharge are repeated.
[0254] Although the embodiments of the present invention are described above, those skilled in the art will understand that various modifications and changes can be made to the present invention by adding, modifying, deleting, increasing, etc., without departing from the scope of the idea of the present invention as described in the claims, and these also fall within the scope of the rights of the present invention.
Claims
1. A positive electrode active material, characterized in that: include: Lithium manganese-based oxides, formed by solid solution or complexation of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group; and The boron-containing compound is physically mixed with the above lithium manganese-based oxide.
2. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide exists in the form of secondary particles formed by agglomeration of a plurality of primary particles, and the boron-containing compound exists independently of the secondary particles.
3. The positive electrode active material according to claim 1, characterized in that The average particle size of the lithium manganese-based oxide is 0.5 μm to 15 μm.
4. The positive electrode active material according to claim 1, characterized in that The average particle size of the boron-containing compound is 50 nm to 80 μm.
5. The positive electrode active material according to claim 1, characterized in that At least a portion of the plurality of lithium manganese-based oxides contained in the positive electrode active material is present in a state of being in physical contact with the boron-containing compound.
6. The positive electrode active material according to claim 1, characterized in that The boron-containing compound may be present in an amount of 0.1 wt % to 3.0 wt % based on the total weight of the positive electrode active material.
7. The positive electrode active material according to claim 1, characterized in that The boron-containing compound includes B2O3, H α B β O γ (0<α<10, 0<β<10, 0<γ<20) and Li α' B β' O γ' At least one of (0<α'<10, 0<β'<10, 0<γ'<20).
8. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide is represented by the following chemical formula 1: [Chemical formula 1] He(He a M1 x M2 y )O 2-b X b (in, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, and M2 and M1 do not repeat, X is a halogen that can replace at least a part of the oxygen present in the lithium manganese-based oxide, <a≤0.7,0≤b≤0.1,0<x≤1,0≤y<1,0<x+y≤1)。 9. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide is represented by the following chemical formula 1-1: [Chemical formula 1-1] rLi2MnO 3-c X' c ·(1-r)Li a' M1 x' M2 y' O 2-b' X b' (in, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, and M2 and M1 do not repeat, X and X' are each independently a halogen capable of replacing at least a portion of the oxygen present in the lithium manganese-based oxide, 0 <r≤0.7,0≤c≤0.1,0<a'≤1,0≤b'≤0.1,0<x'≤1,0≤y'<1,0<x'+y'≤1)。 10. A positive electrode comprising a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, characterized in that: The positive electrode active material layer comprises a positive electrode active material, a boron-containing compound and a conductive material.
11. The positive electrode according to claim 10, characterized in that The lithium manganese-based oxide and the boron-containing compound are present in the positive electrode active material layer in a state of being physically mixed.
12. The positive electrode according to claim 10, characterized in that The positive electrode active material is a lithium manganese-based oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are solid-dissolved or complexed.
13. The positive electrode according to claim 10, characterized in that The average particle size of the boron-containing compound is 50 nm to 60 μm.
14. The positive electrode according to claim 10, characterized in that The content of the boron-containing compound is 0.09 wt % to 3.0 wt % based on the total weight of the solid matter in the positive electrode active material layer.
15. The positive electrode according to claim 10, characterized in that The boron-containing compound includes B2O3, H α B β O γ (0<α<10, 0<β<10, 0<γ<20) and Li α' B β' O γ' At least one of (0<α'<10, 0<β'<10, 0<γ'<20).
16. A lithium secondary battery, characterized in that: The invention comprises the positive electrode according to any one of claims 10 to 15, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte.
Citation Information
Patent Citations
Cathode active material, method for preparing the same, and lithium secondary batteries comprising the same
KR1020150069334A